Hubungan Pengetahuan Gizi Ibu Hamil Dengan Kurang Energi Kronik (KEK) Di Wilayah Kerja Puskesmas Tuminting Kota Manado - Malamtiga, Anisha Deswethasary; Rimporok, Merry R; Sasiwi, Adhe Lisna Gayu (Jurnal Ners, 2025)
Chronic Energy Deficiency (CHD) in pregnant women is a condition where nutritional status is lacking during pregnancy. The problem of CHD in pregnant women is characterized by MUAC <23.5 cm. Knowledge of pregnant women is one of the factors causing the occurrence of CHD. The purpose of this study was to determine the relationship between nutritional knowledge of pregnant women and CHD in the working area of Tumintig Health Center, Manado City. The method used in the study was quantitative with a cross-sectional approach. The population was 125 pregnant women, with a sample size of 56 respondents, and the sample collection method was purposive sampling conducted on April 14-16, 2025. The research instrument used a questionnaire consisting of 28 statements with univariate data analysis using frequency distribution and bivariate analysis using chi-square. The results obtained in this study almost all of respondents were pregnant women aged 20-44 years (91.1%), most of respondents with the last education of SMA / SMK (64.3%), most of respondents did not work (75.0%), and most of respondents did not experience CHD (53.6%). The conclusion of this study obtained the results of the p-value = 0.000, where the p-value <0.05, which means Ha is accepted and H0 is rejected, meaning that there is a relationship between the nutritional knowledge of pregnant women with CHD in the working area of Tuminting Health Center, Manado City. Keywords: Nutrition Knowledge, Chronic Energy Deficiency